Approaches to improve the cultural capabilities of teachers engaging with culturally and linguistically diverse students and their families: a scoping review - Bobongie-Harris, Francis; Youse, Zia (Frontiers in Education, 2023)
This scoping review is the first of three publications that are part of a research project funded by the Queensland Department of Education through their 2021 Horizon Grant funding scheme. This scoping review provides an analysis of contemporary literature that identifies approaches currently being used by educators to successfully engage with culturally and linguistically diverse and Indigenous students, families, and their communities to increase their cultural capabilities. A systemic selection process delivered 21 articles that were included in this Scoping Review. The first four Stages of the study identify and discuss four common areas in which educators can improve cultural capabilities: (i) eldership; (ii) connections; (iii) relationships; (iv) practice. In Stage 5 aspects of these four areas are analyzed in a series of case studies along with an in-depth summary of the literature presented in the scoping review. The literature from this scoping review will inform an engagement strategy that will help improve upon the cultural capabilities of educators working with students in Australian South Sea Islander Communities.